Sistem Informasi Manajemen (SIM) Sebagai Sarana Pencapaian Pembelajaran - Zainal Nur Ali; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
During the stage of development and use of information technology, management information systems (SIMs) have become an important means of education. The SIM helps organize, organize and manage the information needed in the learning process. By using this system, educators and students can easily and quickly access the information they need, which helps facilitate learning and accelerate student progress. In addition, the SIM helps educators manage available resources and resources available to students.